Thermal cycling stability mechanism of Ti50.5Ni33.5Cu11.5Pd4.5 shape memory alloy with near-zero hysteresis. (1st July 2015) - Meng, X.L.; Li, H.; Cai, W.; Hao, S.J.; Cui, L.S.
Abstract : After 5000 thermal cycles, the change of the transformation temperature is less than 1 °C in a Ti50.5 Ni33.5 Cu11.5 Pd4.5 alloy. Also, the hysteresis becomes smaller nearing zero. Using thermal dynamic calculations, the elastic energy is nearly unchanged during the thermal cycles, which means there is little addition of the irreversible energy. The transmission electron microscopy observations show that the irreversible defects such as dislocations are rare in the reciprocating phase transition processes. Both of these explain the high thermal stability mechanism.